Penerapan Model Pembelajaran Two Stay Two Stray dalam Meningkatkan Keaktifan Belajar Pebelajar - Muhammad Mushfi El Iq Bali (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2020)
The study aimed to improve the learning activeness of fourth-grade students through the application of the Two Stay Two Stray learning model. This research design is qualitative research. The instrument of data collection uses observation of teacher and student activities and interviews. The results of the study indicate that: this learning model must form groups of 4 people. Then discuss with the group that has been determined. After discussing, two people from each group visited other groups to get information on the results of discussions from each group. While the task of two members who settled in their group must give the results of their discussion to other groups. The learning process using the learning model Two Stay Two Stray can improve the learning activeness of fourth-grade students of MIN 1 Probolinggo. By using this learning model, students become enthusiastic in learning and they are no longer passive because each individual has their respective duties, so this learning model is declared successful in increasing student learning activeness.